Reduced Bone Stiffness in Women Is Associated with Clinical Attachment and Tooth Loss: The Study of Health in Pomerania. (December 2016) - Silveira, J.L.; Albers, M.; Vargas, D.M.; Santa Helena, E.T.; Cordova, C.M.; Hannemann, A.; Wallaschofski, H.; Meisel, P.; Pink, C.; Samietz, S.; Schmidt, C.O.; Holtfreter, B.; et al.
The authors evaluated the association of reduced bone stiffness of the calcaneus with clinical attachment loss (CAL) and tooth loss. The authors analyzed data from 4, 678 subjects (2, 384 women), aged 20 to 88 y, from the second follow-up of the population-based Study of Health in Pomerania (SHIP-2) and the baseline examination of the SHIP-Trend cohort. Bone stiffness, characterized by the stiffness index (SI) and the osteoporotic fracture risk (OFR), was assessed by quantitative ultrasound of the heel. SI and OFR were significantly associated with the mean CAL in women. While 1) the SI showed a significant association with the mean CAL and 2) the OFR with the median number of teeth in just the postmenopausal women, the OFR showed a significant association with mean CAL for both pre- and postmenopausal women. In postmenopausal women, a 10-unit increase in the SI was associated with a decrease in the mean CAL of 0.05 mm (95% confidence interval [CI]: –0.10 to 0.00; P = 0.046). Moreover, the adjusted median number of teeth was 21.4 (95% CI: 20.9 to 21.9) among the postmenopausal women with a low OFR, while it was 19.1 (95% CI: 17.8 to 20.3; P = 0.001) among the postmenopausal women with a high OFR. For the premenopausal women with a low OFR, the mean CAL was 1.60 mm (95% CI: 1.53 to 1.66), while for the premenopausal women with a high OFR, it was 2.24 mm (95% CI: 1.78 to 2.69; P = 0.006). Reduced bone stiffness was associated with clinical attachment and tooth loss in women but not in men.